On measuring trust and distrust in journalism: Reflection of the status quo and suggestions for the road ahead. Issue 1 (2nd January 2019) - Engelke, Katherine M.; Hase, Valerie; Wintterlin, Florian
ABSTRACT: The rapid advancement of research on trust and distrust in the news media and the plethora of methodological approaches that accompany it leads us to critically reflect the status quo and make suggestions for the road ahead. Following a brief overview of conceptual definitions of trust and distrust as well as of related concepts used in journalism studies, we turn to our main endeavour by presenting measurements used in the field. We identify difficulties in measuring both trust and distrust in journalism and offer suggestions for dealing with them. Specifically, we focus on four main issues: the concept drawn upon for measurement, the employed research design, the object of investigation, and the items and dimensions of measurement. Rather than presenting a finished solution, we hope to advance the methodological consolidation of the field and contribute to the ongoing scholarly debate.